Best Practices & Qualities of Recreational Dementia Friendly Reading Materials - Laskosky, Jennifer (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2021)
Dementia friendly communities have been gaining increased recognition over the years. These communities play a large role in creating opportunities and welcoming spaces for people with dementia. The creation of dementia friendly communities has led to increased development in meaningful dementia friendly experiences including public outings, accessible services, and the creation of dementia friendly reading groups. Despite the effects of dementia, many people with dementia retain their ability to read, even if it is as a lower level. However, reading has remained largely ignored as a meaningful experience for people with dementia. Additionally, there are few resources regarding the creation of dementia friendly reading materials and what is required in order for them to be effective. As a result, there is a lack of appropriate and mature reading materials available for people with dementia. The goal of this study is to determine the necessary qualities of recreational dementia friendly reading materials, through a literature review and case study, and provide best practices for the development of future dementia friendly reading materials. There is a notable lack of research conducted in the library and information studies field, and related fields, regarding recreational dementia friendly reading materials. This study will assist in filling in a gap in the literature and help to establish basic criteria for creating appropriate dementia friendly reading materials.